Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jcu.22568
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical systolic and diastolic dysfunctions in patients with metabolic syndrome and angiographically normal coronary arteries: An echocardiographic study

Abstract: In MetS without coronary artery disease, echocardiography demonstrated subclinical systolic and diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the MetS group, BMI and waist circumference were significantly higher than the healthy subjects. This is in line with the data from Samiei et al, who concluded significantly greater BMI and waist circumferences amongst participants with MetS [23].…”
Section: Discussionsupporting
confidence: 92%
“…In the MetS group, BMI and waist circumference were significantly higher than the healthy subjects. This is in line with the data from Samiei et al, who concluded significantly greater BMI and waist circumferences amongst participants with MetS [23].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the prognostic value of fQRS in patients with cardiovascular diseases, it has also been found to be associated with subclinical myocardial dysfunction in patients with coronary artery disease, diabetes mellitus, and chronic kidney disease . The assessment of myocardial tissue by conventional echocardiography is load‐ and angle‐dependent, but 2‐dimensional speckle‐tracking echocardiography (2D‐STE) lacks such a limitation for the evaluation of myocardial mechanics . Although left ventricular ejection fraction (LVEF) is commonly used for the evaluation of LV function, 2D‐STE parameters, mainly global longitudinal strain (GLS), have been found to be a feasible modality for examination of left ventricle (LV) function …”
Section: Introductionmentioning
confidence: 99%
“…19 The assessment of myocardial tissue by conventional echocardiography is load-and angle-dependent, but 2-dimensional speckle-tracking echocardiography (2D-STE) lacks such a limitation for the evaluation of myocardial mechanics. [20][21][22][23] Although left ventricular ejection fraction (LVEF) is commonly used for the evaluation of LV function, 2D-STE parameters, mainly global longitudinal strain (GLS), have been found to be a feasible modality for examination of left ventricle (LV) function. 24 In this case-control study, we sought to determine the relationship between the presence of fQRS in apparently healthy individuals without cardiovascular diseases and preserved LVEF and subclinical LV dysfunction using 2-dimensional transthoracic echocardiography (2D-TTE) with the implementation of tissue Doppler imaging (TDI) and speckle-tracking echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, clinical and subclinical systolic and diastolic dysfunction have been demonstrated by echocardiography in MS patients without coronary artery disease ( 4 , 5 ). Furthermore, LV diastolic dysfunction, instead of systolic dysfunction, has been associated with limited exercise capacity independent of ischemia ( 6 ).…”
Section: Introductionmentioning
confidence: 93%